Mental Health Burden and Resilience among Nigerians undergoing COVID-19 Isolation in Kaduna-Nigeria - Abiola, Tajudeen; Ibrahim, Muhammad Gidado; Yakasai, Bashir Adam; Yusuf, Abdulkareem Jika; Hayatudeen, Nafisa; Lubuola, Issa Bamidele; Fajimolu, Olugbenga Ola (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: The coronavirus pandemic and Its “pandemic-fear,” is expected to come with lots of mental health challenges. Despites several global health vanguards sounding this alarm, there is paucity of systematic analysis of mental health distress and resilience being experienced by individuals undergoing treatments in isolation centres for coronavirus disease (COVID-19).Objectives: This study evaluated the pattern of mental distress and resilience in COVID-19 patients undergoing isolation-care in some treatment facility in Kaduna-Nigeria.Method: Data were collected cross-sectionally from 261 participants. These were sociodemographic and clinical variables, measures of mental distress (i.e. depression and anxiety), and well-being (i.e. resilience). Statistical analysis was carried out using SPSS version 21.Results: The mean age of participants was 35.6 years (SD = 11.1), with majority being males (73.6%) and without prior chronic medical condition (73.9%). Mental distress rates were 33.0% for depression and 19.2% for anxiety. Majority (97.1%) had good resilience characteristics. Significant variable associated with low mental distress and high resilience is belonging to age group 40 years and above. Also, resilience was moderately and significantly related to mental distress.Conclusion: Mental distress is relatively high among COVID-19 patients undergoing isolation-treatment. This rate is associated with age group of below 40 years and having low resilience characteristics. Efforts to boost resilience among COVID-19 might institute preventive measures against mental distress.